Pemanfaatan hutan dan program pengembangan pemukiman transmigrasi sebagai usaha pengembangan wilayah (Direktorat Tata Kota dan Tata Daerah, 1981)
On the cost effectiveness of using profits from wood felled at transmigration sites to finance area development.